2018
DOI: 10.1039/c8cc03614d
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 binds to the KRAS promoter G-quadruplex: a new player in oncogene transcriptional regulation?

Abstract: This communication reports on a possible distinct role of HMGB1 protein. Biophysical studies revealed that HMGB1 binds and stabilizes the G-quadruplex of the KRAS promoter element that is responsible for most of the transcriptional activity. Biological data showed that inhibition of HMGB1 increases KRAS expression. These results suggest that HMGB1 could play a role in the gene transcriptional regulation via the functional recognition of the G-quadruplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…The NHE in the KRAS proximal promoter is highly abundant in G-rich sequences, and several transcription factors interact with a G4 structure formed in this region (Figure 8a) [176,177,178]. A polypurine G-rich element, located approximately –300 to –100 nucleotides upstream of the exon 0/intron 1 boundary in a murine or human genome, is likely to be a component of the promoter activity, and includes multiple PQSs [45,46,176,177,178,179,180]. Importantly, pyrene-modified oligonucleotides that were devised to be a more stable form of the KRAS G4 formed in the PQS1 were able to attract the factors essential for transcription and to exhibit a strong antiproliferative activity through a G4-decoy effect in pancreatic cancer cells [181].…”
Section: Cancer-related G-quadruplexes and Their Interacting Molecmentioning
confidence: 99%
“…The NHE in the KRAS proximal promoter is highly abundant in G-rich sequences, and several transcription factors interact with a G4 structure formed in this region (Figure 8a) [176,177,178]. A polypurine G-rich element, located approximately –300 to –100 nucleotides upstream of the exon 0/intron 1 boundary in a murine or human genome, is likely to be a component of the promoter activity, and includes multiple PQSs [45,46,176,177,178,179,180]. Importantly, pyrene-modified oligonucleotides that were devised to be a more stable form of the KRAS G4 formed in the PQS1 were able to attract the factors essential for transcription and to exhibit a strong antiproliferative activity through a G4-decoy effect in pancreatic cancer cells [181].…”
Section: Cancer-related G-quadruplexes and Their Interacting Molecmentioning
confidence: 99%
“…HMGB1 has been identified as a binding partner of telomeric G4 in a pull‐down assay and the initial in vitro comparative studies with promoter G4s confirmed HMGB1 selectivity for the telomeric quadruplex structure . However, subsequent studies revealed that HMGB1 also has a high affinity for the KRAS promoter G4 . While most noncanonical DNA structures are unwound by HMGB1, G4s are not (for the KRAS G4, substantial HMGB1‐induced stabilization was reported).…”
Section: G4s Might Directly Engage Architectural Chromatin Proteins mentioning
confidence: 99%
“…However, subsequent studies revealed that HMGB1 also has a high affinity for the KRAS promoter G4 . While most noncanonical DNA structures are unwound by HMGB1, G4s are not (for the KRAS G4, substantial HMGB1‐induced stabilization was reported).…”
Section: G4s Might Directly Engage Architectural Chromatin Proteins mentioning
confidence: 99%
“…Figure 2 shows SPR sensorgrams obtained by injecting increasing concentrations of GROs over the nucleolin-functionalized sensor-chip surface by using the single-cycle kinetics (SCK) method. SCK was preferred to the multi-cycle kinetics because, using this method, the regeneration step (which is detrimental to the protein) is performed only at the end of the complete binding cycle, thus allowing the chip surface and immobilized protein to last longer [ 35 , 36 ]. The GROs (analytes) were injected from a low to high concentration with short dissociation times in between and a long dissociation time at the end.…”
Section: Resultsmentioning
confidence: 99%